Evaluation of deep sedation effects and respiratory aspects of remimazolam besylate in elderly patients undergoing fiberoptic bronchoscopy - Ma, Dongmei; Li, Li; Han, Fuyi; Xu, Jianhong; Zhang, Cheng (Frontiers in Medicine, 2025)
BackgroundThe geriatric population, especially individuals over 65 years old with comorbidities classified by the ASA (American Society of Anesthesiologists) grading system, requires careful sedation management during flexible bronchoscopy (FB) to reduce the heightened risks of complications. Hypoxemia is a particularly critical concern in this demographic, leading to considerable morbidity, mortality, and increased healthcare costs. This study focuses on comparing the incidence of sedation-related hypoxemia and other adverse events between remimazolam besylate and propofol during FB procedures, aiming to enhance patient safety and optimize sedation practices in this vulnerable population.MethodsThis prospective observational cohort study compared the incidence of hypoxemia and sedation-related adverse events between remimazolam besylate and propofol in 69 elderly patients (ASA I-III). Rigorous inclusion/exclusion criteria, clinical monitoring, and alongside comprehensive monitoring of clinical parameters and statistical analyses to ensure the validity of the results.ResultsHypoxemia occurred in 44.90% overall, with significantly lower incidence in remimazolam besylate cohort (29.42% vs. 60.00%; OR = 2.10, 95% CI 1.18–3.74, p = 0.017). Recovery to full alertness was prolonged with remimazolam (median 15[12.5–20] vs. 8[5.5–10] min; p < 0.001). A trend toward reduced hypotension was observed (17.65% vs. 37.14%, p = 0.0699), with no other significant safety differences.ConclusionRemimazolam besylate demonstrates superior safety for elderly FB sedation, significantly reducing hypoxemia risk and accelerating recovery. These findings support its preferential use in geriatric sedation protocols, warranting further investigation to optimize clinical implementation strategies.